A review of vitamin D and its effects on athletes - Watkins, C. M.; Lively, M. W. (The Physician and Sportsmedicine, 2012)
Research into vitamin D has revealed the important role it plays in a variety of biologic functions. Despite this importance, vitamin D deficiency remains one of the most underdiagnosed conditions in the world. Although no evidence exists that athletes have a higher daily requirement than the general population, vitamin D deficiency in athletic individuals has been linked to decreased physical performance and a predisposition to stress fractures. Research investigating ergogenic effects of direct vitamin D supplementation in non-deficient athletes has yet to be performed. This review discusses the current evidence on the effects of vitamin D in athletes, along with recommended strategies for the correction of deficient states.